Biochar-mediated transformation of titanium dioxide nanoparticles concerning TiO2NPs-biochar interactions, plant traits and tissue accumulation to cell translocation. (1st February 2021) - Abbas, Qumber; Yousaf, Balal; Mujtaba Munir, Mehr Ahmed; Cheema, Ayesha Imtiyaz; Hussain, Imran; Rinklebe, Jörg
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) application in variety of commercial products would likely release these NPs into the environment. The interaction of TiO2 NPs with terrestrial plants upon uptake can disturb plants functional traits and can also transfer to the food chain members. In this study, we investigated the impact of TiO2 NPs on wheat ( Triticum aestivum L.) plants functional traits, primary macronutrients assimilation, and change in the profile of bio-macromolecule. Moreover, the mechanism of biochar-TiO2 NPs interaction, immobilization, and tissue accumulation to cell translocation of NPs in plants was also explored. The results indicated that the contents of Ti in wheat tissues was reduced about 3-fold and the Ti transfer rate (per day) was reduced about 2 fold at the 1000 mg L −1 exposure level of TiO2 NPs in biochar amended exposure medium. Transmission electron microscopy (TEM) with elemental mapping confirmed that Ti concentrated in plant tissues in nano-form. The interactive effect of TiO2 NPs + biochar amendment on photosynthesis related and gas exchange traits was observed at relatively low TiO2 NPs exposure level (200 mg L −1 ), which induced the positive impact on wheat plants proliferation. TiO2 NPs alone exposure to wheat also modified the plant's bio-macromolecules profile with the reduction in the assimilation of primary macronutrients, which could affect the food crop nutritional value and quality. X-ray photoelectron spectroscopy (XPS) chemical analysis of biochar + TiO2 NPs showed an additional peak, which indicated the binding interaction of NPs with biochar. Moreover, Fourier-transform infrared (FTIR) spectroscopy confirmed that the biochar carboxyl group is the main functionality involved in the bonding process with TiO2 NPs. These findings will help for a mechanistic understanding of the role of biochar in the reduction of NPs bioavailability to primary producers of the terrestrial environment. Graphical abstract: Image 1 Highlights: Investigated the mechanism of TiO2 NPs interaction with biochar. TEM confirmed the plant uptake of titanium in nano-form. TiO2 NPs modified the bio-macromolecules and nutritional profile of wheat. Biochar addition reduced the titanium accumulation about 3-folds in wheat tissues. Biochar based carboxyl groups mediated the transformation of TiO2 NPs.